Hidrolisis Pati Sukun dengan Katalisator H2SO4 untuk Pembuatan Perekat - Lubis, Mirna Rahmah (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2012)
Breadfruit starch is a unique resource which benefits for raw material of adhesive making. This study investigates hydrolysis method of breadfruit starch into dextrin with Sulphate Acid (H2SO4) catalysator. Dextrin hydrolysis is carry out in order to produce high dextrin percentage by subtracting the total glucose with free glucose. This study evaluates composition change because of breadfruit starch in various time and temperature. Optimum dextrin percentage is obtained at hydrolysis temperature of 100C, hydrolysis time 10 minutes, and 0.5 N H2SO4 concentration, with dextrin percentage of 77.12%. Furthermore, dextrin obtained is added by casein, cold water, triethanolamine, and water in order to form adhesive. The reserch result showed that the shear strength of the dextrin glue is 14 kg/cm2 which is larger than that of glue of Fox brands sold in the market that is only 12.48 kg/cm2. Because there is previous study regarding starch hydrolysis from breadfruit by using chloride acid catalysator, then data in this research show the influence of the sulphate acid usage as catalysator of adhesive. Based on the comparison, it seems that for breadfruit starch hydrolyzed at 100oC for 10 minutes, dextrin produced is less than that obtained by using chloride acid catalysator. The less dextrin percentage from breadfruit starch is caused by not all hydro sulphate ions are dissociated while mixing with starch. The mass balance is necessary to be completed including analysis of the breadfruit starch composition after hydrolysis to determine whether the starch has been degraded or not.Keywords: adhesive, dextrin, hydrolysis, shear strength